Profiling the mental characteristics of sub-elite marathon runners - Coumbe-Lilley, J. E.; Hamstra-Wright, K. L.; Weidner, A. (The Sport Journal, 2015)
There has been considerable increase in the number of participants running marathons between 1990 and 2014 with the majority of runners between 23-54 years of age (Running USA, 2015). With the increase in the number of people and the range of abilities running marathons, it is important to the field of sport psychology to understand the preparatory, performance, and recovery needs of this group of athletes. The primary purpose of our institutional review board approved study was to describe the psychological skills profile of sub-elite marathon competitors to understand the important mental qualities leading runners to complete a marathon. The secondary purpose was to draw conclusions for future applied sport psychology intervention research.